Concepciones históricas en torno a la infancia: una lectura necesaria para comprender el presente (2016)
Some historical conceptions formed a place for childhood in different periods for the sake of understanding childhood. The present paper analyzes childhood and family in the classical world, the medieval child, the childhood Psychogenic Theory and the childhood feeling in the modern society. Likewise, some childhood conceptions facing the Piaget contributions in the Cognitive Revolution setting and its incidence in the education field are presented as well as a general panorama in front of the international legislations in favor of childhood from the inherited conceptions of it to the looking after and protecting to their recognizing as social subject performers of their own growth with inalienable rights in their full individual potential.However, although the legislations about this social group, they are turned into indicators that refer to the progress in front of the recognizing of children as citizens today. The advances in front of their fulfillment are threatened by the child situations in vulnerable individual conditions for the full exercise of their rights